Modelisation de I' evolution des fonds mobiles en mer et en riviere par elements finis - Dhatt, Gouri; Tanguy, Jean-Michel; Peltier, Eric; Zhang, Bainian (European Journal of Computational Mechanics, 1994)
Sediment transport, under waves and currents action, modify bed topography of rivers, estuaries and seas, by means of deposition and erosion processes. The aim of this article is to compare two numerical schemes, used to discretise the bed continuity equation, in the context of the finite element method. The first one is a Lax-Wendroff type scheme and the other one is based on the characteristic method.